P239 Pre-analytical DNA yield and variability influences microbiome laboratory analysis. (19th June 2022) - Kumar, Aditi; Segal, Jonathan; Steed, Helen; Janke, Detlef; Gravdal, Kristin; Brookes, Matthew; Al-Hassi, Hafid O
Abstract : Background: Next-generation sequencing (NGS) has revolutionised genomics research and become increasingly cost-effective. However, there are numerous confounding variables that affect data consistency and reproducibility, particularly in the pre-analytical steps. This study compared two DNA extraction methods from the same faecal samples to analyse differences in microbial composition. Methods: Faecal samples were collected from twenty patients at the Royal Wolverhampton NHS Trust, UK. DNA was extracted using either (A) mechanical (bead-beating) or (B) chemical (heat) lysis. Fifty-four DNA probes targeting >300 bacteria on different taxonomic levels were selected based on their 16S rRNA sequence (V3-V9). Apart from the pre-analytical DNA extraction technique, all other parameters including microbial analysis remained the same for all the samples. Bacterial abundance and deviations in the microbiome from normobiosis were recorded and compared between the two methods (A and B). Results: Whilst there was no difference seen in bacterial species variation, there was significant variation in bacterial abundance between the different DNA extraction techniques, with a higher yield of species noted in the mechanical lysis technique (A). The five predominant bacteria seen in both (A) and (B) were Bacteroidota spp & Prevotella spp showing a mean platform signal strength of 735 and 565 respectively (p=NS), followed by Bacillota (614 vs 362, p=0.005), Lachhnospiraceae (814 vs 460, p=0.0001), Veillonella spp (570 vs 182, p<0.0001) and Clostridioides (439 vs 152, p<0.0001) ( Figure 1 ). Conclusion: As microbial testing becomes more easily and commercially accessible, a unified international consensus for optimal sampling and DNA isolation procedures must be implemented for robustness and reproducibility of results.